Click, get, learn 2.0: A digital learning framework grounded in learning styles to foster the advancement of student-centered learning - Pramitha, Devi; Anggarini, Ida Fitri; Anjani, Yulia Iva; Salsabila, Haya (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
In the era of Society 5.0, the learning paradigm has significantly shifted from teacher-centered learning toward student-centered learning. The optimization of student-centered learning can be achieved through various approaches; however, one of the potential implementations explored in this study is the use of a digital learning framework. This research aims to examine the effectiveness of a learning style–based framework in daily teaching and learning activities. The study employs a quasi-experimental method with a pre-test and post-test control group design. The population consists of 30 twelfth-grade students from the Research Program at MA Al-Ittihad Poncokusumo in the 2025/2026 academic year, selected using a purposive sampling technique. Learning style categorization was conducted using the VARK Learning Style Inventory questionnaire (5-point Likert scale), followed by learning activities tailored to the identified styles without class separation. Changes in understanding were measured through pre-tests and post-tests, each comprising five questions. The results of the experimental group revealed that the average increase in both comprehension and post-test skill scores was higher than in the pre-test. This finding demonstrates that the application of a digital framework aligned with the learning system can lead to significant improvements in the learning process.